Preparation method and application of water treatment catalyst with low oxidant consumption
By converting natural diatomaceous earth into a catalyst composed of nanoscale pore enrichment and silicon oxygen bonds (Si/C@BD), the problems of high oxidant consumption and resource-intensive synthesis in the prior art are solved, and the effects of low oxidant consumption and high-efficiency pollutant degradation are achieved.
Patent Information
- Application Number
- CN202411833706.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
Existing water treatment catalysts have problems with high oxidant consumption and resource-energy-intensive synthesis processes, making it difficult to achieve sustainable harmless water treatment, especially in complex aquatic ecosystems.
Using natural diatomaceous earth and dopamine hydrochloride as raw materials, the water treatment catalyst composed of nanoscale pore enrichment and silicon oxygen bonds (Si/C@BD) is prepared, and pollutant degradation is carried out using extremely low peroxygen monosulfate (PMS).
It realizes rapid degradation of pollutants at extremely low PMS usage, reduces oxidant consumption and energy costs, and the catalyst is degradable and has a wide range of applications.
Smart Images

Figure CN119633790A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a preparation method and application of a low oxidant consumption water treatment catalyst. Background Art
[0002] In recent years, peroxymonosulfate-based advanced oxidation processes (PMS-AOPs) have attracted increasing attention in the field of water treatment. This is because PMS-AOPs can generate a series of reactive oxygen species (ROS) with strong oxidative capacity by activating PMS. Since the generated ROS have relatively high redox potentials (e.g., SO4 2- 2.5-3.1 V (compared to NHE) and HO·1.9-2.7 V (compared to NHE). However, the introduction of strong oxidants and ROS into water may cause indiscriminate damage to aquatic organisms and ecosystems. In addition, the catalysts and the generated byproducts (e.g., Fe 3+ 、SO4 2- etc.) are potentially hazardous, leading to secondary pollution problems. Although there are some focuses on less environmentally vulnerable methods such as non-radical AOPs, achieving harmless in situ water treatment remains a major challenge, especially for surface streams with complex aquatic ecosystems. Therefore, it is crucial to develop a sustainable Fenton treatment process based on the use of low oxidants.
[0003] Currently, many catalysts have been developed to reduce the amount of oxidants and achieve efficient degradation of pollutants at the same time, including high metal loading or high metal dispersion catalysts (such as single atom catalysts, SACs) and dual reaction center (DRC) preparation procedures based on electron-deficient / electron-rich regions. For example, it was found that the complexation of metals and organic supports through the formation of cation-π bonds is beneficial to induce electron redistribution on the catalyst surface and construct DRCs with electron-rich / electron-poor microcenters. The unique electron transfer / circulation at the DRC interface not only improves the utilization of oxidants, but also utilizes the energy of pollutants, significantly reducing the resource and energy consumption in the catalyst application stage. However, the preparation strategies of these catalysts still rely on the addition of a large amount of high-cost raw materials, and the synthesis processes and strategies are often not universal. The resource- and energy-intensive stages of catalyst synthesis are still difficult to overcome, which is in serious contradiction with the concept of sustainable development. Summary of the invention
[0004] Based on the above technical problems, the present invention proposes a preparation method and application of a water treatment catalyst with low oxidant consumption.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a water treatment catalyst with low oxidant consumption comprises the following steps:
[0007] a. Select natural diatomaceous earth and dopamine hydrochloride as raw materials, add natural diatomaceous earth into water, and prepare diatomaceous earth suspension;
[0008] b. Add dopamine hydrochloride to the diatomaceous earth suspension, then adjust the pH value of the solution and stir to react;
[0009] c. collecting the reaction products and annealing them under an inert atmosphere to obtain a precursor;
[0010] d. The precursor was immersed in hydrofluoric acid for etching, then filtered, rinsed with deionized water until neutral, and dried to obtain a water treatment catalyst (Si / C@BD).
[0011] Preferably, in step a: the concentration of the diatomaceous earth suspension is 8-15 g / L.
[0012] Preferably, in step b: the mass ratio of dopamine hydrochloride to natural diatomaceous earth is 1:3-7.
[0013] Preferably, in step b: Tris-HCl is used to adjust the pH value of the solution to 8-9.
[0014] Preferably, in step b: the reaction time is controlled to be 10-20h.
[0015] Preferably, in step c: annealing is controlled at 700-900°C for 1-5h under N2 atmosphere, with a heating rate of 5-10°C / min. That is, the temperature is raised from room temperature to 700-900°C at a heating rate of 5-10°C / min under N2 atmosphere, and treated at this temperature for 1-5h, and then cooled naturally.
[0016] Preferably, in step d: the concentration of hydrofluoric acid is 10wt%-30wt%; and the etching time is 12-36 hours.
[0017] Preferably, in step d: drying is controlled under vacuum conditions, the drying temperature is 60-70° C., and the drying time is 5-7 hours.
[0018] The water treatment catalyst prepared by the above method can cooperate with peroxymonosulfate (PMS) to degrade pollutants in water.
[0019] The peroxymonosulfate is preferably used in an amount of 0.05-0.1 mM.
[0020] The pollutants include tetracycline, bisphenol A, metronidazole and p-nitrobenzoic acid, etc.
[0021] The beneficial technical effects of the present invention are as follows:
[0022] The present invention converts diatomite into a water purification catalyst composed of nano-scale pores enriched with silicon-oxygen bonds (Si / C@BD). Tests have shown that the catalyst can rapidly degrade pollutants by amplifying the electron transfer process (ETP) of Si / C@BD at extremely low peroxymonosulfate (PMS) usage.
[0023] The present invention innovatively uses diatomaceous earth as a raw material to prepare the catalyst. Diatomaceous earth is a natural material. The prepared catalyst can reduce the consumption of oxidant. At the same time, the method reduces the energy and cost used for water purification and realizes the recycling of natural materials. It has a wide range of applications and is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic flow diagram of a method for preparing a water treatment catalyst with low oxidant consumption according to the present invention;
[0025] Figure 2 This is a scanning electron microscope image of the catalyst Si / C@BD prepared in Example 1 of the present invention;
[0026] Figure 3 This is the pore size distribution diagram of the catalyst Si / C@BD prepared in Example 1 of the present invention;
[0027] Figure 4 TEM image of the catalyst Si / C@BD prepared in Example 1 of the present invention;
[0028] Figure 5 TEM EDS mapping of pores in the catalyst Si / C@BD prepared in Example 1 of the present invention;
[0029] Figure 6 The pore parameter comparison chart of different samples;
[0030] Figure 7 The degradation of TC and PMS consumption in Si / C@BD / PMS system under different PMS usage are shown;
[0031] Figure 8 The degradation of TC by different catalysts is shown (PMS dosage: 0.1 mM; TC concentration: 10 mg / L). DETAILED DESCRIPTION
[0032] Many natural materials have some potential universal catalytic sites. For example, the porous structure of some natural materials can efficiently enrich pollutants and oxidants as well as various reactive oxygen species (ROS) with strong oxidizing ability, effectively reduce the migration distance of ROS and promote the efficient degradation of pollutants, and have high activity characteristics similar to constrained catalysis. In natural materials, especially in carbon-based materials, doping with relatively weak negatively charged heteroatoms, such as N, B, O, S, Si, etc., can effectively adjust the electronic structure of carbonaceous materials and generate new active sites, thereby significantly improving the catalytic performance of carbonaceous materials. These heteroatoms are inherent in some natural materials and can be transferred to available active sites to achieve effective Fenton-like oxidation. Diatomaceous earth (DE) is a common and low-cost natural clay mineral, mainly composed of amorphous silicon dioxide (SiO2), with rich silanol (Si-O) groups and a special three-dimensional porous hollow structure. The introduction of Si-O bonds in the preparation of carbon-based catalysts by template method is conducive to the generation of new active sites, while improving the electronic structure of carbon-based catalysts, thereby significantly improving the catalytic performance. Based on this, the present invention proposes a sustainable strategy involving the conversion of diatomite into a water purification catalyst composed of nano-sized regular pores enriched and silicon-oxygen bonds (Si / C@BD). The results show that at extremely low PMS usage, Si / C@BD can rapidly degrade pollutants through the electron transfer process (ETP) as the main reaction pathway, and its catalytic activity is superior to most reported catalysts. This strategy can also be applied to other catalytic systems derived from silicon-based materials.
[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0034] Example 1
[0035] First, the natural diatomite DE was acid-washed to remove the organic matter and trace metal oxides present, and then dopamine hydrochloride (0.4 g) was completely dissolved in the DE suspension (10 g / L, 200 ml), followed by the addition of 1 ml of Tris-HCl (1 M, pH = 8.8) for pH adjustment. After stirring for 16 h, the dopamine monomer can be polymerized on the surface of the disc-shaped DE to form a disc-shaped dopamine shell, which was collected and annealed at 800 ° C for 2 h under N2 atmosphere to form a precursor. Subsequently, the diatomite template was etched by immersing the Si / C@BD precursor in hydrofluoric acid (20 wt%) for 24 h. The deposit was then filtered and rinsed with deionized water several times to neutrality, and dried under vacuum at 60 ° C for 6 h to collect Si / C@BD.
[0036] Example 2
[0037] First, the natural diatomite DE was acid-washed to remove the organic matter and trace metal oxides present, and then dopamine hydrochloride (0.6 g) was completely dissolved in the DE suspension (10 g / L, 200 ml), followed by the addition of 1 ml of Tris-HCl (1 M, pH = 8.8) for pH adjustment. After stirring for 10 h, the dopamine monomer can be polymerized on the surface of the disc-shaped DE to form a disc-shaped dopamine shell, which was collected and annealed at 900 ° C for 1 h under N2 atmosphere to form a precursor. Subsequently, the diatomite template was etched by immersing the Si / C@BD precursor in hydrofluoric acid (30 wt%) for 24 h. The deposit was then filtered and rinsed with deionized water several times to neutrality, and dried under vacuum at 70 ° C for 5 h to collect Si / C@BD.
[0038] Example 3
[0039] First, the natural diatomite DE was acid-washed to remove the organic matter and trace metal oxides present, and then dopamine hydrochloride (0.3 g) was completely dissolved in the DE suspension (10 g / L, 200 ml), followed by the addition of 1 ml of Tris-HCl (1 M, pH = 8.8) for pH adjustment. After stirring for 20 h, the dopamine monomer can be polymerized on the surface of the disc-shaped DE to form a disc-shaped dopamine shell, which was collected and annealed at 700 ° C for 5 h under N2 atmosphere to form a precursor. Subsequently, the diatomite template was etched by immersing the Si / C@BD precursor in hydrofluoric acid (10 wt%) for 36 h. The deposit was then filtered and rinsed with deionized water several times to neutrality, and dried under vacuum at 65 ° C for 7 h to collect Si / C@BD.
[0040] Example 4
[0041] First, the natural diatomite DE was acid-washed to remove the organic matter and trace metal oxides present, and then dopamine hydrochloride (0.4 g) was completely dissolved in the DE suspension (8 g / L, 200 ml), and then Tris-HCl (1 M) was added to adjust the pH to 8. After stirring for 16 h, the dopamine monomer can be polymerized on the surface of the disc-shaped DE to form a disc-shaped dopamine shell, which was collected and annealed at 800 ° C for 2 h under N2 atmosphere to form a precursor. Subsequently, the diatomite template was etched by immersing the Si / C@BD precursor in hydrofluoric acid (20 wt%) for 24 h. The deposit was then filtered and rinsed with deionized water several times to neutrality, and dried under vacuum at 60 ° C for 6 h to collect Si / C@BD.
[0042] Example 5
[0043] First, the natural diatomite DE was acid-washed to remove the organic matter and trace metal oxides present, and then dopamine hydrochloride (0.5 g) was completely dissolved in the DE suspension (15 g / L, 200 ml), and then Tris-HCl (1 M) was added to adjust the pH to 9. After stirring for 18 h, the dopamine monomer can be polymerized on the surface of the disc-shaped DE to form a disc-shaped dopamine shell, which was collected and annealed at 850 ° C for 2 h under N2 atmosphere to form a precursor. Subsequently, the diatomite template was etched by immersing the Si / C@BD precursor in hydrofluoric acid (20 wt%) for 24 h. The deposit was then filtered and rinsed with deionized water several times to neutrality, and dried under vacuum at 70 ° C for 6 h to collect Si / C@BD.
[0044] Figure 1 This is a flow chart of the method for preparing the catalyst Si / C@BD using natural diatomite DE in the present invention. Figure 2 This is a scanning electron microscope (SEM) image of the catalyst Si / C@BD prepared in Example 1 of the present invention. According to the image, compared with natural DE, Si / C@BD exhibits a similar porous disc-shaped structure. Figure 3 This is the pore size distribution diagram of the catalyst Si / C@BD prepared in Example 1 of the present invention. It can be seen from the figure that the pore size distribution range is 100 to 800 nm, and the average pore size is 294.3±17.0 nm. Figure 4 This is a TEM image of the catalyst Si / C@BD prepared in Example 1 of the present invention. Figure 5 TEM EDS mapping of the pores in the catalyst Si / C@BD prepared in Example 1 of the present invention. Figure 4 and Figure 5 It can be seen that Si / C@BD and DE with the same surface structure exhibit completely different chemical compositions. EDS mapping of Si / C@BD shows that it is composed of carbon elements, doped with only a small amount of silicon and oxygen. In contrast, natural DE is mainly composed of silicon and oxygen elements. These results indicate that the silica shell of DE is removed by hydrofluoric acid etching, but the characteristic disk morphology composed of Si-O doped carbon-based structure is retained. The TEM image of Si / C@BD can clearly show the outward-contracted to inward pore structure in Si / C@BD. In addition, the Si / C@BD EDS mapping based on HAADF-STEM image confirms that the pores in Si / C@BD are mainly composed of C elements with dispersed Si-O structure. X-ray diffraction (XRD) of DE and Si / C@BD shows specific peaks assigned to quartz crystals, which disappear in Si / C@BD. Therefore, Si / C@BD will remove quartz crystals by etching, retaining the biomorphic porous disk-like structure of DE, in which the carbon component is dominant. The pore characteristics of Si / C@BD show that the BET surface area and pore volume are 132.43 m 2 / g and 0.23cm 3 / g( Figure 6 ), which is nearly 100 times higher than DE and the precursor. This is because the high-density silicon-based substrate in the precursor is etched, leaving only the porous hollow disk carbon structure. In comparison, universal etched silicon-based catalysts (Si / C@BM and Si / C@SiO2) were prepared using montmorillonite and spherical SiO2 as templates. The BET surface areas of similar catalysts derived from montmorillonite (Si / C@BM) and SiO2 (Si / C@SiO2) ranged from 67.38 to 89.32 m 2 / g.
[0045] In addition, X-ray photoelectron spectroscopy (XPS) also showed that the chemical composition of Si / C@BD and DE changed significantly. DE showed very high Si (31.35at%) and O (55.79at%) components, while Si (0.97at%) and O (8.84at%) in Si / C@BD were significantly reduced, with the C component dominating (86.18at%). Compared with O1 of DE, in addition to the Si-O bonds of DE, more abundant oxygen groups (C=O and CO) can be observed in O1 of Si / C@BD. In addition, compared with DE, new peaks assigned to CO-Si bonds were observed in Si 2p of Si / C@BD, which indicates that Si-O bonds have been coordinated to the carbon framework of Si / C@BD.
[0046] The degradation of TC and the consumption of PMS in the Si / C@BD / PMS system under different PMS usage conditions are shown in Figure 2. Figure 7 As shown, the results indicate that Si / C@BD can almost completely remove TC with a low PMS usage rate (0.1mM), with a PMS consumption efficiency of over 88%. In contrast, the PMS consumption efficiency significantly decreased to 45-65% with the increase of PMS (0.25 and 0.5mM). This means that Si / C@BD can achieve a higher utilization rate of PMS for TC oxidation at a lower PMS dosage (0.1mM), and the residual PMS (0.012mM) remaining in the matrix is only 4-13% compared with the PMS dosage of 0.25-0.5mM (0.090-0.293mM). Therefore, the Si / C@BD / PMS system can effectively reduce the PMS dosage while realizing an economical, efficient and low-pollution PMS catalytic system. The degradation of TC by natural DE and unetched samples (precursors) was approximately 42.0% and 67.6%, and the degradation rate (k obs ) are 0.018 and 0.045min respectively -1 In contrast, TC can be rapidly oxidized by common etched samples (Si / C@BD, Si / C@BM, Si / C@SiO2) at 0.1 mM PMS, k obsRange: 0.115-0.190min -1 ,like Figure 8 shown.
[0047] The excellent oxidation activity of the low oxidant consumption water treatment catalyst Si / C@BD prepared in the present invention may be due to its more regular pore structure and abundant Si-O bonds, which are used to enrich pollutants and PMS and subsequent activation reactions. Si / C@BD degrades different pollutants by activating PMS (0.1mM) and shows high degradation selectivity under three different degradation rate gradients.
[0048] In addition, by normalizing k obs Compared with the standardized PMS usage, the results show that the metal-free Si / C@BD prepared in Example 1 of the present invention can achieve very high degradation performance, far exceeding most reported metal-free catalysts, traditional metal species and metal / carbon composites with low PMS usage. - 、SO4 2- 、NO3 - 、HPO4 2- ), humic acid (HA) and cations (Na + , K + Mg 2+ , Ca 2+ ) in the presence of Si / C@BD / PMS system, the TC degradation in the Si / C@BD / PMS system remained stable (0.31-0.33 min -1 ); This indicates that the Si / C@BD / PMS system can resist the interference of external environmental media. The degradation of TC can also be carried out in different pH ranges, except for the case of pH 11.0, which shows that the k obs From 0.33min -1 Down to 0.28min -1 This may be due to the electronegativity of the catalyst surface under alkaline conditions, which leads to electrostatic repulsion with PMS and pollutants. It is known that the heating process can promote the activation of PMS and promote the PMS kinetic process on the catalyst interface. Therefore, the degradation of TC under different temperature conditions is affected by k obs When the temperature rises from 20℃ to 40℃, k obs From 0.33min -1 Increased to 0.42min -1 .
[0049] In summary, the extensive use of persulfate and the resulting sulfate pollution are the main bottlenecks of persulfate-based advanced oxidation systems. In this work, a sustainable strategy is proposed to transform diatomite into a metal-free catalyst composed of nanoscale pore-enriched and silicon-oxygen bonds (Si / C@BD). The results show that the obtained Si / C@BD can rapidly degrade pollutants at very low PMS stoichiometric doses via an amplified ETP process. The nano-regular-sized pores in Si / C@BD will enrich pollutants and PMS in a limited space and enhance mass transfer to achieve (i) an amplified ETP pathway with strong anti-interference and oxidation selectivity (ii) ultrafast "low oxidant consumption" Fenton-like chemistry. This strategy is also applicable to other catalytic systems derived from silicon-based natural materials. The gaps between the HOMO and LUMO of Si-OC / PMS of different pollutants and their lnk obs The data (R2 = 0.89) and ΔE1 and instantaneous current showed a good linear correlation. These results confirm the high degradation selectivity and low PMS consumption of Si / C@BD-based ETP oxidation.
Claims
1. A method for preparing a low oxidant consumption water treatment catalyst, characterized in that The following steps are involved: a. Select natural diatomaceous earth and dopamine hydrochloride as raw materials, add natural diatomaceous earth into water, and prepare diatomaceous earth suspension; b. Add dopamine hydrochloride to the diatomaceous earth suspension, then adjust the pH value of the solution and stir to react; c. collecting the reaction products and annealing them under an inert atmosphere to obtain a precursor; d. Immerse the precursor in hydrofluoric acid for etching, then filter it, rinse it with deionized water until it is neutral, and dry it to obtain a water treatment catalyst.
2. The method for preparing a low oxidant consumption water treatment catalyst according to claim 1, characterized in that: In step a: the concentration of the diatomaceous earth suspension is 8-15 g / L.
3. The method for preparing a low oxidant consumption water treatment catalyst according to claim 1, characterized in that: In step b: the mass ratio of dopamine hydrochloride to natural diatomaceous earth is 1:3-7.
4. The method for preparing a low oxidant consumption water treatment catalyst according to claim 1, characterized in that: In step b: Tris-HCl is used to adjust the pH value of the solution to 8-9.
5. The method for preparing a low oxidant consumption water treatment catalyst according to claim 1, characterized in that: In step b: the reaction time is controlled to be 10-20h.
6. The method for preparing a low oxidant consumption water treatment catalyst according to claim 1, characterized in that: In step c: annealing is controlled at 700-900°C for 1-5h under N2 atmosphere, with a heating rate of 5-10°C / min.
7. The method for preparing a low oxidant consumption water treatment catalyst according to claim 1, characterized in that: In step d: the concentration of hydrofluoric acid is 10wt%-30wt%; and the etching time is 12-36 hours.
8. The method for preparing a low oxidant consumption water treatment catalyst according to claim 1, characterized in that: In step d: drying is controlled under vacuum conditions, the drying temperature is 60-70° C., and the drying time is 5-7 hours.
9. The water treatment catalyst prepared by any one of the methods of claims 1 to 8 can cooperate with peroxymonosulfate to degrade pollutants in water.
10. The application method according to claim 9, characterized in that: The dosage of the peroxymonosulfate is 0.05-0.1 mM.